PENINGKATAN KUALITAS PELAYANAN UNTUK MENJAMIN KEBERLANGSUNGAN USAHA PADA BENGKEL ZUL KELUARGA JAYA PEMATANGSIANTAR - Efendi Efendi; Marto Silalahi; Julyanthry Julyanthry; Vivi Candra; Hendrick Sasimtan Putra; Onita Sari Sinaga (Universitas YPPI Rembang, 2024)
The community service activity focusing on the socialization of service quality improvement at Bengkel Zul Keluarga Jaya Pematangsiantar is important to provide additional knowledge to the owners and employees of the workshop, as well as strategies to increase sales turnover. The methods used include lectures and discussions related to the service quality improvement topic. The implementation stages of the event include an opening and explanation of the good and correct services commonly used by companies. After the activity, further interviews were conducted to evaluate the impact of the activity. The results of the interviews showed that the understanding of the owners and employees of Bengkel Zul Keluarga Jaya regarding service quality to ensure business sustainability increased by 90%.